2020
DOI: 10.1002/cam4.3650
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the preoperative systemic immune‐inflammation index in patients with oral cavity squamous cell carcinoma treated with curative surgery and adjuvant therapy

Abstract: Objectives To investigate the prognostic value of the preoperative systemic immune‐inflammation index (SII) in patients with oral cavity squamous cell carcinoma (OC‐SCC) treated with curative surgery followed by adjuvant radiotherapy (RT) or chemoradiotherapy (CCRT). Materials and Methods We retrospectively reviewed the clinical records of patients with OC‐SCC who received surgery and postoperative adjuvant RT/CCRT between January 2005 and December 2012. Blood samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Many reports, including systematic reviews, have shown the usefulness of NLR, PLR, and MLR as prognostic predictors in the eld of head and neck cancer (13,14,15). Conversely, few studies have reported the usefulness of SIRI and SII in this eld, and the usefulness of SIRI in nasopharyngeal cancer and SII in oral cancer has been reported (16,17). Neutrophils participate in various processes of tumor growth through cytokine production (18) and promote tumor angiogenesis by releasing angiogenic factors (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Many reports, including systematic reviews, have shown the usefulness of NLR, PLR, and MLR as prognostic predictors in the eld of head and neck cancer (13,14,15). Conversely, few studies have reported the usefulness of SIRI and SII in this eld, and the usefulness of SIRI in nasopharyngeal cancer and SII in oral cancer has been reported (16,17). Neutrophils participate in various processes of tumor growth through cytokine production (18) and promote tumor angiogenesis by releasing angiogenic factors (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…This biomarker is used as a prognostic factor in diseases with inflammation-related causes . The SII has also recently been highlighted as a predictor of mortality for head and neck as well as other cancers …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a number of inflammatory biomarkers (IBs) and their derived ratios have been investigated as prognostic indicators in various cancers. The systemic immune inflammation index (SII), an integrated indicator based on peripheral lymphocyte, neutrophil, and platelet counts, is a strong prognostic indicator for patients with several tumor types ( 13 ). Recent studies have revealed that higher neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are associated with poorer outcomes in ESCC ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%